Needs analysis of Islamic-based English reading material for the Muhammadiyah junior high school - Septian Dwi Cahyo; Muhammad Rijalul Umam Muslim; Arditya Nur Rahman; Bambang W Pratolo (International Journal of Evaluation and Research in Education (IJERE), 2019)
This research aimed to report the need for Islamic-based English teaching materials for the Muhammadiyah junior high Schools, specified for reading skill. Data collection techniques in this research were the semi-structured interview and focus group discussion with four English teachers as participant form the Muhammadiyah schools. Data analysis was conducted by interactive data collection, data reduction, data presentation and conclusion or verification. This research concluded that the needs of developing Islamic based English teaching material are necessary for the Muhamamadiyah schools to achieve the national education goal and for Islamic faith itself. The development based on text-based approach by replacing content with Islamic-related content, Islamic discourse, integrated language skill, use student-centered teaching and also increasing cultural awareness.